PELATIHAN ECOENZYME SEBAGAI SOLUSI OLAH SAMPAH DARI RUMAH - Aprida, Siti Nurul; Sanjaya, Tantri Mega; Adawiyah, Robiatul; Adindan, Wiwik; Safira, Mutia (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
Waste disposal that is not properly managed will result in big problems for human life, because it can result in a source of pollution and environmental pollution which can be dangerous for health. The aim of this service is to socialize how to manage household waste into ecoenzymes which provide many benefits as well as being an alternative to save on cleaning costs and daily living. The method used in this research is lectures and discussions, as well as direct practice at the service location. Based on the research results, it was found that all training participants were able to follow and understand the process of making ecoenzyme from organic waste from fruit and vegetable peels, as well as reducing environmental pollution from organic waste